2019
DOI: 10.1037/bul0000205
|View full text |Cite
|
Sign up to set email alerts
|

Defending behavior of peer victimization in school and cyber context during childhood and adolescence: A meta-analytic review of individual and peer-relational characteristics.

Abstract: Adolescent defending of peer victimization in the school and cyber context has received increased attention in developmental science and is an important component of antibullying interventions. However, the overall prevalence, and individual characteristics that correlate with defending in adolescence, have not been systematically and statistically reviewed. Framed in Bronfenbrenner’s social-ecological theory, this meta-analytic review included 172 reports out of 155 studies of defending including 150,978 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 176 publications
8
54
0
Order By: Relevance
“…This finding is similar to other studies that found younger students tend to engage more as proactive bystanders than older students (e.g. Bellmore et al 2012;Ma et al 2019) and rates of passive bystander behaviour (or doing nothing) increase with age (Trach et al 2010). Increasing levels of bullying victimisation, peer support and school connectedness and lower moral disengagement, in particular diffusion of responsibility, distortion of consequences of being bullied, and blaming the bullying target, were associated with higher odds of a proactive bystander response.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is similar to other studies that found younger students tend to engage more as proactive bystanders than older students (e.g. Bellmore et al 2012;Ma et al 2019) and rates of passive bystander behaviour (or doing nothing) increase with age (Trach et al 2010). Increasing levels of bullying victimisation, peer support and school connectedness and lower moral disengagement, in particular diffusion of responsibility, distortion of consequences of being bullied, and blaming the bullying target, were associated with higher odds of a proactive bystander response.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the Ma et al (2019) and Killer et al (2019) metaanalyses, the present study found overall moral disengagement to be associated with a decreased odds of a defending or proactive response to bullying. Contrary to the hypotheses, gender did not moderate the relationship between moral disengagement and defending behaviour, and thereby failed to replicate the findings of Thornberg and Jungert (2013) and Doramajian and Bukowski (2015).…”
Section: Moral Disengagementsupporting
confidence: 81%
See 1 more Smart Citation
“…Researchers and anti-bullying organisations are increasingly investigating the individual and situational predictors of defender responses amongst young people (Ma, Meter, Chen, & Lee, 2019; van der Ploeg, Kretschmer, Salmivalli, & Veenstra, 2017; Yun & Graham, 2018) as well as attending to the development and evaluation of programmes to promote defender responses in schools (Salmivalli, Kärnä, & Poskiparta, 2010; Timmons-Mitchell, Levesque, Harris, Flannery, & Falcone, 2016). For example, the successful KiVa programme is the largest anti-bullying programme to acknowledge the importance of training bystanders.…”
mentioning
confidence: 99%
“…That is, bullying was considered a special form of peer victimization (e.g., "bullying is recognized as a subset of peer victimization that is intentional, chronic, and characterized by an imbalance of power between victim and aggressor", Felix et al, 2011, p. 234). Students who are targets of bullying victimization, compared to students who are targets of peer victimization, fare worse on several dimensions (Hunter et al, 2007;Malecki et al, 2015;Oblath et al, 2019;van der Ploeg et al, 2015;van Noorden et al, 2016;Ybarra et al, 2014). Even so, critical voices have been raised that being overly adherent to or focused on the concept of bullying might lead researchers to ignore children's negative social interactions that do not meet the three bullying criteria (Finkelhor et al, 2012;Fry et al, 2020;Turner et al, 2015).…”
Section: Introduction Peer Victimization: Definition Prevalence Andmentioning
confidence: 99%